Pengaruh Employer Branding, Work Engagement, dan Career Development Terhadap Retensi Karyawan Generasi Z di PT Charoen Pokphand - Latul Munawaroh, Lia; Sulhan, M. (Jurnal Administrasi Bisnis Nusantara, 2026)
Employee retention among Generation Z has become a strategic challenge for companies in the digital era, especially given the dynamics of a younger workforce that demands more than just financial compensation. This generation is known to prefer workplaces with a strong employer image, a supportive work environment, and clear career development opportunities. This study aims to examine the influence of Employer Branding, Work Engagement, and Career Development on the retention of Generation Z employees. A quantitative approach was used, employing a survey method with 20 respondents who are Generation Z employees at PT Charoen Pokphand. Data were collected using structured questionnaires and analyzed through multiple linear regression using SPSS version 26. The F-test results show that the independent variables collectively have a significant influence on employee retention, with an F_calculated value of 917.798 and a significance value of 0.000. Partial test results also indicate that each variable individually has a significant effect. Employer Branding recorded a t_calculated value of 4.219 (p = 0.000), Work Engagement at 3.764 (p = 0.001), and Career Development at 3.840 (p = 0.000). These findings suggest that an effective retention strategy cannot rely on a single factor but must integrate employer image, strong employee engagement, and well-structured career development programs. The study concludes that a holistic approach to human resource management is essential for sustainably retaining talented young employees